NEGOTIATING FAITH, FUTURE, AND FOREIGN LANGUAGE: A PSYCHOLOGICAL INQUIRY INTO ENGLISH LEARNING AMONG NON-ENGLISH MAJOR STUDENTS AT AN ISLAMIC UNIVERSITY - Liah Rosdiani Nasution; Sandi Pradana; Iis Maisaroh; Selvi Ratna Sari; Sri Andayani (University of Kuningan, 2025)
In religious university environments, the development of English-speaking skills among non-English major students presents unique psychological and contextual challenges. Ideally, students should be able to integrate language mastery with their religious and academic identity to face global demands. However, empirical findings reveal that many students experience high anxiety, lack of confidence, and inconsistent institutional support, particularly in the informal learning environment of the Ma’had program. Through a qualitative inquiry involving in-depth interviews, this study identifies four major themes: (1) Psychological Barriers in Speaking English, (2) Contextual Gaps between Academic Programs and Dormitory Initiatives, (3) Adaptive and Maladaptive Coping Strategies, and (4) Students' Aspirations for Effective English Learning Environments. The research highlights that although formal academic programs provide structured learning, the informal settings often lack systematic reinforcement, leading to fragmented experiences in language acquisition. Students express a strong need for a more integrated, empathetic, and motivational approach in both academic and dormitory settings. This study contributes to the theoretical understanding of English learning in faith-based institutions and offers practical implications for curriculum designers, language instructors, and religious educational policymakers aiming to bridge the psychological and contextual gaps. The findings advocate for the design of supportive programs that not only build linguistic competence but also align with students’ religious values and future aspirations, fostering a more holistic development of English proficiency in faith-driven academic environments.